Pelatihan Digital Marketing dan Social Media Tools - Achmad Ridha; Wiwin Riski Windarsari; Nurazizah Rahmi R; Ardiansyah Ardiansyah; Fina Ruzika Zaimar (Universitas Ichsan Sidenreng Rappang, 2025)
In today's digital era, marketing transformation from conventional to digital methods is an urgent need, especially for Micro, Small, and Medium Enterprises (MSMEs). Many MSMEs have not optimally utilized digital platforms to expand their market reach. This community service activity aims to improve the understanding and skills of MSMEs in using digital marketing strategies and utilizing social media tools effectively. The methods used are interactive training, direct practice, and case studies. The results of the activity showed an increase in participants' knowledge in identifying target markets, managing digital content, and optimizing platforms such as Instagram, Facebook, and WhatsApp Business. This activity is expected to be the first step in encouraging sustainable digital transformation of MSMEs.